Attenuation of miR-34a protects cardiomyocytes against hypoxic stress through maintenance of glycolysis. Issue 6 (6th November 2017) - Zhang, Ying; Liu, Gang; Gao, Xiaogang
Abstract : MiRNAs are a class of endogenous, short, single-stranded, non-coding RNAs, which are tightly linked to cardiac disorders such as myocardial ischemia/reperfusion (I/R) injury. MiR-34a is known to be involved in the hypoxia-induced cardiomyocytes apoptosis. However, the molecular mechanisms are unclear. In the present study, we demonstrate that under low glucose supply, rat cardiomyocytes are susceptible to hypoxia. Under short-time hypoxia, cellular glucose uptake and lactate product are induced but under long-time hypoxia, the cellular glucose metabolism is suppressed. Interestingly, an adaptive up-regulation of miR-34a by long-time hypoxia was observed both in vitro and in vivo, leading to suppression of glycolysis in cardiomyocytes. We identified lactate dehydrogenase-A (LDHA) as a direct target of miR-34a, which binds to the 3′-UTR region of LDHA mRNA in cardiomyocytes. Moreover, inhibition of miR-34a attenuated hypoxia-induced cardiomyocytes dysfunction through restoration of glycolysis. The present study illustrates roles of miR-34a in the hypoxia-induced cardiomyocytes dysfunction and proposes restoration of glycolysis of dysfunctional cardiomyocytes by inhibiting miR-34a during I/R might be an effectively therapeutic approach against I/R injury.